Novel capsular diversity and antimicrobial resistance determinants of Staphylococcus aureus associated with bovine and bubaline mastitis - Ghafoor, M.; Saqib, M.; Ashfaq, K.; Rehman, S.U. (Polish Journal of Veterinary Sciences, 2026)
In Pakistan, bovine mastitis has been identified as one of the biggest limitations to dairy production, and Staphylococcus aureus has been identified as one of the most enduring and economically relevant mastitogens. The current study was conducted to examine the capsular genotype and antimicrobial resistance (AMR) of S. aureus isolated from cases of clinical and subclinical mastitis in cows and buffaloes of the Punjab and Sindh provinces. One hundred and fifty S. aureus isolates (109 from cows and 41 from buffaloes) were isolated out of 87 dairy herds and verified using nuc gene-based PCR. Genotyping of capsular polysaccharide (CP) demonstrated that there were only cap5 (56%) and cap8 (44%) loci, but no cap1 and cap2. The cap5 was the most common among clinical (20.66%) and subclinical (35.33%) isolates, whereas cap8 had a frequency of 12.66% and 31.33% in clinical and subclinical isolates, respectively, suggesting that CP5 and CP8 are the common circulating types of capsular pathogens in the study areas. The antimicrobial susceptibility testing involving 13 routine antimicrobial agents revealed that 92% of isolates were resistant to one or more antimicrobials, and 63.3% of the isolates were multidrug-resistant (MDR). The greatest resistance was found with penicillin (72.66%), then amoxicillin (53.33%), and amoxicillin-clavulanic acid (37.33%). Those resistant to methicillin (3.33%) were mecA-positive MRSA, but no isolate was positive for mecC. Molecular screening showed that the prevalence of the blaZ gene (95.33%) was high and in line with the prevalence of resistance mediated by β-lactamase. The tetM (92.10%) and tetK (84.21%) were most common among the tetracycline-resistant isolates. The determinants of macrolide resistance were msrC (87.5%), ermB and ermC, and the aac-aphD aminoglycoside resistance gene was also present in 17.64% of resistant isolates. Resistance to critically important antimicrobials like vancomycin and linezolid was low, and optrA was not identified. Strong genotype-phenotype concordance was shown by correlation analysis to occur in 22 cases where 2 beta-lactam, tetracycline, and macrolide resistance determinants were genotyped and phenotyped, indicating the occurrence of co-selection and possible horizontal gene transfer. This study provides the first comprehensive molecular epidemiological insight in bovine and bubaline S. aureus capsular diversity, as well as AMR determinants of S. aureus, in Punjab and Sindh. The prevalence of CP5/CP8 is in favor of their inclusion in vaccine development, whereas high rate of MDR burden evidences the urgency of antimicrobial stewardship and long term molecular surveillance within one health paradigm.